Heterogeneity in time preference in older households - Antoine Bozio; Guy Laroque; Cormac O'Dea (Institute for Fiscal Studies (IFS), 2013)
This paper suggests a method for estimating the distribution of discount rates using panel data on income and wealth. Using the English Longitudinal Survey of Ageing (ELSA), a representative sample of the English popularion over age 50, we general panel date on total consumption from the intertemporal budget constraint. The distribution of consumption levels is shown to closely match that estimated using the UK's household budget survey. Consumption transitions over time are then used to estimate the discount rates of households. We show that there is substantial heterogeneity in discounting behaviour and find that, among this older population, households with less education or numerical ability exhibit greater patience than those with higher education or numerical ability. The direction of this association is the opposite to that which has been found in experimental investigations of time preference.
Keywords: D12; D31; D91; E21; 330; time preference; discount rate; heterogeneity; consumption